PSYCHOLOGICAL REHABILITATION OF RETURN MIGRANTS: PRACTICAL APPROACHES - Ergasheva Mazluma Xusan qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores the psychological rehabilitation of return migrants, focusing on practical approaches that facilitate their social and emotional reintegration. The study highlights common psychological challenges faced by returnees, such as stress, cultural adjustment difficulties, and social isolation. It examines effective therapeutic methods, including cognitive-behavioral therapy, group counseling, and community support programs, emphasizing culturally sensitive and holistic rehabilitation strategies. The article concludes with recommendations for improving access to mental health services and strengthening support systems for return migrants.